“Adjust Zang and arouse spirit” electroacupuncture ameliorates cognitive impairment by reducing endoplasmic reticulum stress in db/db mice - Li, Mengyuan; Yao, Lin; He, Min; Huang, Haipeng; Zheng, Haizhu; Ma, Shiqi; Zhong, Zhen; Yu, Shuo; Sun, Mengmeng; Wang, Hongfeng (Frontiers in Endocrinology, 2023)
Diabetic cognitive impairment (DCI) is a chronic complication of the central nervous system (CNS) caused by diabetes that affects learning and memory capacities over time. Recently, acupuncture has been shown to improve cognitive impairment in streptozotocin-induced diabetic rats. However, the effects of electroacupuncture on DCI and its underlying mechanism have not yet been elucidated in detail. In this study, we used db/db mice as DCI animal models which showed low cognitive, learning and memory functions. Electroacupuncture significantly ameliorated DCI, which is reflected by better spatial learning and memory function using behavioral tests. Moreover, electroacupuncture attenuated diabetes-induced morphological structure change, neuronal apoptosis in the hippocampus of db/db mice. Our results revealed that electroacupuncture could regulate the expression levels of Tau and Aβ by improving hippocampal ERS levels in db/db mice, inhibiting JNK activation, attenuating IRS1 serine phosphorylation, and restoring normal transduction of the insulin signaling pathway. In summary, ERS and insulin signaling pathway paly causal roles in DCI development. This study adds to our understanding of the effect of acupuncture on DCI and opens the door to further research on DCI.